Intra-industry trade, involuntary unemployment and macroeconomic stability - Riche, Antoine Le (2021)
We introduce taste for variety in a one-sector model of differentiated products with productive labor externalities, considering two OLG countries, one with wage rigidity and the other with full employment. After opening the borders to capital mobility and intra-industry trade, steady state output and real wages improve in the full employment country and the saddle path stability, characterizing this country under autarky, will prevail in the globalized world if this economy is big enough. Unemployment increases in the country with wage rigidity and, for intermediate plausible values of both the current propensity to consume and of the labor externality, indeterminacy, which emerges in the rigid wage economy in autarky, will be exported to the world if this country is relatively big. Finally, we show that globalization leads to the appearance of stable deterministic cycles in activity, employment and the trade account, both through flip and Hopf bifurcations, when the world steady state is locally determinate, for empirically plausible low degrees of labor externalities. This implies that trade cycles occur in the absence of shocks to fundamentals, and even without uncertainty in expectations.